Morphometric investigations of fresh and fixed rabbit kidney - Durmuş Bolat; Sadullah Bahar; Muhammet Lutfi Selçuk; Sadettin Tipirdamaz (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study was to investigate the effect of formalin fixation on the morphometry of kidneys, and to assess the volume and fractions of its constituents using the Cavalieri principle. Materials and Methods: In this study, kidneys of nine healthy male White New Zealand rabbits were used. After weighing the kidneys, craniocaudal length, and mediolateral and dorsoventral diameters of fresh kidneys were measured with digital calipers, and the volume of each kidney was estimated using Archimedes' principle. The fresh kidneys were kept in a container of 10% formalin solution for 15 days. The Cavalieri principle was utilized for the determination of volume and the volume fraction of renal constituents. Results: The differences in the dorsoventral diameter of fresh (15.8±0.26 mm) and fixed (14.8±0.32 mm) right kidneys were found to be statistically significant (p<0.05). The relative organ weights were determined to be 0.38±0.02% and 0.38±0.01% for the left and right kidneys, respectively. After formalin fixation, the weights of the left and right kidney increased by 7.33% and 7.56% respectively, and an increase in volume was determined between fresh and fixed left (7.13%, p<0.05) and rightkidneys (3.34%, p>0.05). Conclusion: It is believed that obtained morphometric data will contribute to studies involving the investigation of kidney diseases using invasive and non-invasive methods.